2015
DOI: 10.1016/j.jcot.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infection in orthopedic trauma: A case–control study evaluating risk factors and cost

Abstract: a b s t r a c tBackground: With the shift of our healthcare system toward a value-based system of reimbursement, complications such as surgical site infections (SSI) may not be reimbursed.The purpose of our study was to investigate the costs and risk factors of SSI for orthopedic trauma patients.Methods: Through retrospective analysis, 1819 patients with isolated fractures were identified. Of those, 78 patients who developed SSIs were compared to 78 uninfected control patients. Patients were matched by fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
95
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 24 publications
5
95
1
5
Order By: Relevance
“…They also encounter higher direct and indirect health care costs. The results from a recent cost analysis showed that the hospital-related health care costs of infected cases are approximately 6.5-times higher than for non-infected cases, which is much higher than data that were previously published [24]. These results stress the importance of standardized prevention and treatment guidelines, with respect to this serious complication.…”
Section: Introductionmentioning
confidence: 91%
“…They also encounter higher direct and indirect health care costs. The results from a recent cost analysis showed that the hospital-related health care costs of infected cases are approximately 6.5-times higher than for non-infected cases, which is much higher than data that were previously published [24]. These results stress the importance of standardized prevention and treatment guidelines, with respect to this serious complication.…”
Section: Introductionmentioning
confidence: 91%
“…Surgical site infection (SSI) is one of the most common complications in orthopaedic surgery, and its incidence was reported to vary greatly depending on the definitions of infection, fracture locations and sites, surgical patterns, and the study design. SSIs incresed the possibility of abscess formation, osteomyelitis, and bone union problems, which might have long‐term negative effects on the mobility of the unjured limbs or articular joints .…”
Section: Introductionmentioning
confidence: 99%
“…SSIs incresed the possibility of abscess formation, osteomyelitis, and bone union problems, which might have long‐term negative effects on the mobility of the unjured limbs or articular joints . On the other hand, postoperative SSIs substantially increased the total medical costs because of secondary surgery or antibiotic treatment and prolonged hospitalisation stay by 7 to 14 days . Therefore, identification of the associated risk factors and their use in the comprehensive assessment of patients' susceptibility to SSIs, thereby screening patients at risk, could be a simple and cost‐effective measure to reduce or prevent SSI occurrence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of infection after internal fixation of closed fractures is reported to be 1-2% but can reach 30% in cases of open fractures [5][6][7]. As the consequences of such infection can be life-changing for the patient due to permanent functional loss or amputation of the affected limb, patient quality of life (QoL) and functional status also decrease [8][9][10]. To tackle these issues, it seems highly important to focus on infection prevention and improve outcome.…”
Section: Introductionmentioning
confidence: 99%